Financial strategy analysis for china shenhua energy company limited - Zhen, Jiang; K. Widhaningrat, Sisdjiatmo (The Indonesian Journal of Business Administration, 2018)
Abstrak. This paper focus on financial strategy which plays a crucial role. Financial analysis is only method that can provide the statistics data to help entrepreneur make decisions. The objectives of analyzing the appropriate financial strategy to revitalize the company growth and improve the company’s performance health. Shenhua is china biggest coal dealer and the company with 20 years history, and is the leader of the coal industry and has succeful experience on innovation and transformation on other industry. Shenhua model is the main business strategy which intergrated the sales of coal, railway, transportation as well as power generation. The business model made the company become large-scale,high efficient and safe production mode in china’s coal industry. This research uses the secondary data completion analysis. The second data is that from company’s data as well public disclourse output. Using du pont business analysis module to evalute the company’s performance. During research, the paper will use solvency analysis, company efficiency analysis, financial quality analysis and risk analysis. After reasearch,  the researchor want to give some recommentions to the entrepreneur,such as: improve cash flow management and financing management, financial planning, internal control, risk management.Key word :shenhua, strategic, du pont analysis,  financial ratio, improvement